2021
DOI: 10.3892/ijmm.2021.4960
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps promote gastric cancer metastasis by inducing epithelial‑mesenchymal transition

Abstract: The risks of tumor recurrence following the successful resection of the primary tumor have been known for decades; however, the precise mechanisms underlying treatment failures remain unknown. The formation of neutrophil extracellular traps (NETs) has increasingly been demonstrated to be associated with thrombi formation in cancer patients, as well as with the development and metastasis of cancer. The present study demonstrated that the level of peripheral blood NETs in patients with gastric cancer (Gc) was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 58 publications
6
78
0
1
Order By: Relevance
“…NETs promote migration ability in breast cancer through EMT [ 90 ]. This result is consistent with another study in GC [ 106 ]. It shows that process of EMT is significant for NETs induced tumor metastasis.…”
Section: Nets and Cancersupporting
confidence: 94%
“…NETs promote migration ability in breast cancer through EMT [ 90 ]. This result is consistent with another study in GC [ 106 ]. It shows that process of EMT is significant for NETs induced tumor metastasis.…”
Section: Nets and Cancersupporting
confidence: 94%
“…NETs also promote the process of metastasis by contributing to migration and invasion by tumor cells [18,24,44]. It has been recently shown that, in gastric cancer, NETs promote a more aggressive mesenchymal phenotype [45]. Park et al [41] demonstrated that more neutrophils were recruited in the context of murine metastatic breast cancer cells (4 T1) when compared with cells that did not metastasize.…”
Section: Intratumoral Nets and Netosis In Cancer Progressionmentioning
confidence: 99%
“…A study comparing triple-negative human breast cancer (oestrogen− progesterone−, HER-2−) with luminal HER-2+ breast cancer found excessive NET formation in the case of triple-negative human breast cancer that correlated with the spread of metastases [103]. In patients with stage III/IV gastric cancer, the NET density was significantly higher compared with healthy donors and patients with stage I/II of the disease, while no significant differences in NET density were found between patients with stage III or IV of the disease [98]. The late stages of breast and lung cancer were characterized by higher NET density compared with the early stage [99,103].…”
Section: Pro-tumor and Antitumor Effects Of Netsmentioning
confidence: 96%
“…Large accumulations of dead neutrophils and NETs have been found in the microenvironment of haemorrhagic lungs in LLC mice, Ewing's sarcoma, small bowel cancer, colorectal cancer, breast cancer and lymphoma [92][93][94][95][96][97]. Patients with advanced lung, breast or gastric cancer are characterized by excessive formation of NETs and, moreover, research also indicates that NET levels may be associated with metastasis [98,99]. Some authors suggest that NET deposition in tumor tissue may have a cytotoxic effect.…”
Section: Pro-tumor and Antitumor Effects Of Netsmentioning
confidence: 99%